QOLP-38. PATIENT REPORTED OUTCOMES IN GLIOMA: THE ROLE OF IDH MUTATION ON QUALITY OF LIFE AND MOOD. (11th November 2019) - Parsons, Michael; Bunevicius, Adomas; Dietrich, Jorg
Abstract: : Isocitrate dehydrogenase 1 (IDH) mutation has important clinical prognostic value in glioma patients conferring improved survival and better neurocognitive function (NCF) compared to IDH wild type (IDH-WT) patients. It is not known whether IDH mutation status has an impact on patient reported outcomes (PRO). The goal of this single institution retrospective study was to examine the impact of IDH-mutation status on PRO's in patients who also completed neuropsychological evaluation. METHODS: Out of 101 glioma patients referred for neuropsychological evaluation between 2018–2019, 73 completed the Functional Assessment of Cancer Therapy-Brain (FACT-Br; non-completion due to severe cognitive impairment, poor English). In addition to the total score, the FACT-Br includes 5 subscales of wellbeing (Physical, Social, Emotional, Functional, and Brain specific symptoms). 69 patients completed the Beck Depression Inventory (BDI) and 61 completed the Beck Anxiety Inventory (BAI). Self-reported symptoms were compared between those with IDH-Mut vs IDH-WT by ANOVA. RESULTS: Diagnoses included glioblastoma (20), diffuse astrocytoma grade II/III (29) and oligodendroglioma grade II/III (24). 29/73 (40%) patients were IDH-mut. FACT-Br total scores did not differ between IDH-WT and IDH-Mut glioma patients (F=2.685; p=ns). Separate analyses of the 5 FACT-Br subscales showed that only the emotional functioning subscale differed significantly, with IDH-Mut patients reporting better emotional functioning than IDH-WT patients (F=7.4; p< 0.05). BDI and BAI scores did not differ by group (F= 2.2 and 1.9, respectively; p=NS). CONCLUSIONS: IDH mutation was related to patient reported emotional status on the FACT-Br in this mixed clinical sample of glioma patients. Analysis is complicated by the heterogeneity of the sample and retrospective nature of the study. Routine inclusion of PRO's as standard of care may allow a more comprehensive understanding of the impact of IDH throughout the natural history of glioma.